Molecular interplay of pro-inflammatory transcription factors and non-coding RNAs in esophageal squamous cell carcinoma - Gopinath M Sundaram; Pallaval Veera Bramhachari (Tumor Biology)
Esophageal squamous cell carcinoma is the sixth most common cancer in the developing world. The aggressive nature of esophageal squamous cell carcinoma, its tendency for relapse, and the poor survival prospects of patients diagnosed at advanced stages, represent a pressing need for the development of new therapies for this disease. Chronic inflammation is known to have a causal link to cancer pre-disposition. Nuclear factor kappa B and signal transducer and activator of transcription 3 are transcription factors which regulate immunity and inflammation and are emerging as key regulators of tumor initiation, progression, and metastasis. Although these pro-inflammatory factors in esophageal squamous cell carcinoma have been well-characterized with reference to protein-coding targets, their functional interactions with non-coding RNAs have only recently been gaining attention. Non-coding RNAs, especially microRNAs and long non-coding RNAs demonstrate potential as biomarkers and alternative therapeutic targets. In this review, we summarize the recent literature and concepts on non-coding RNAs that are regulated by/regulate nuclear factor kappa B and signal transducer and activator of transcription 3 in esophageal cancer progression. We also discuss how these recent discoveries can pave way for future therapeutic options to treat esophageal squamous cell carcinoma.